Head-to-head comparison of 68Ga-PSMA-11 and 18F-FDG in delayed PET/CT imaging in prostate cancer diagnosis - Hu, Biyao; Yu, Haonan; Pan, Meijie; Yang, Hailei; Xing, Xiling; Li, Dong; Yao, Shaobo; Chen, Qiusong (Frontiers in Oncology, 2025)
PurposeDelayed PET/CT imaging with 68Ga-PSMA-11 is valuable in the detection of primary prostate (PCa) lesions and the differentiation of suspicious lesions. However, 18F-FDG PET/CT has been overlooked due to its low sensitivity to PCa during routine examination. This study aimed to compare the clinical impact of PSMA and FDG in delayed PET/CT imaging in PCa diagnosis.MethodsBetween 2019 and 2024, 65 PCa patients who underwent early (1 h post-injection) and delayed (3 h p.i.) PSMA and FDG scans were retrospectively analyzed. The delayed scans were conducted to clarify unclear findings in early scans or to increase the tumor lesions uptake in negative early scans. All patients were asked to drink 1 L of water between early and delayed scans. The number of primary and metastatic lesions, sensitivity, specificity, diagnostic accuracy, lesions changes in SUVmax of early and delayed scans were evaluated. Correlation between SUVmax and Gleason score as well as SUVmax and PSA for PCa primary lesions diagnosis were analyzed.ResultsOverall, 83 and 84 lesions characteristic for PCa in 65 patients clearly presented at 1 h and 3 h p.i. in PSMA scans, respectively. 30 and 45 lesions characteristic for PCa in 65 patients clearly presented at 1 h and 3 h p.i. in FDG scans. The 3-hour delayed imaging of FDG found more primary foci than 1-hour imaging but was much less able to detect metastatic foci than PSMA. PSMA was more sensitive than FDG in delayed imaging (96.15% vs. 84.21%), and the diagnostic accuracy for primary foci was higher for PSMA than FDG in delayed imaging (83.87% vs. 73.91%). However, FDG delayed imaging greatly improved the diagnostic accuracy for primary PCa compared to early imaging (73.91% vs.53.33%). PSMA SUVmax of both 1 h and 3 h p.i. were correlated with the Gleason score PSA, but FDG SUVmax only showed a correlation with PSA at 3 h p.i.ConclusionPSMA PET/CT at 3 h p.i. detected the most lesions characteristic of primary PCa, and it showed higher uptake and contrast than FDG. However, to some extent, FDG delayed PET/CT imaging is still important in primary PCa diagnosis, particularly in hospitals without PSMA.